2019
DOI: 10.1371/journal.pone.0211237
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of potential ovicidal natural products using metabolomics

Abstract: Plant extracts are a potential source of new compounds for nematode control and may be an excellent alternative for the control gastrointestinal nematodes that are resistant to conventional anthelmintics. However, research involving natural products is a complex process. The main challenge is the identification of bioactive compounds. Online analytical techniques with universal detectors, such as high-performance liquid chromatography-mass spectrometry (HPLC-MS), together with metabolomics could enable the fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
3
18
0
1
Order By: Relevance
“…The current study demonstrated the presence of triterpenoids, including oleanolic acid, ursolic acid, the representative pentacyclic triterpenes, and their derivatives ( 1 – 8 ). The anthelmintic activity of L. asiatica is thought to be exerted by triterpenoids because several reports demonstrated that oleanolic acid and ursolic acid possessed anthelmintic activity [39,40], and saponins were also associated with the ovicidal action of the plant extract [41]. Thus, this study supports the evidence for clarifying the anthelmintic effect of L. asiatica .…”
Section: Resultssupporting
confidence: 85%
“…The current study demonstrated the presence of triterpenoids, including oleanolic acid, ursolic acid, the representative pentacyclic triterpenes, and their derivatives ( 1 – 8 ). The anthelmintic activity of L. asiatica is thought to be exerted by triterpenoids because several reports demonstrated that oleanolic acid and ursolic acid possessed anthelmintic activity [39,40], and saponins were also associated with the ovicidal action of the plant extract [41]. Thus, this study supports the evidence for clarifying the anthelmintic effect of L. asiatica .…”
Section: Resultssupporting
confidence: 85%
“…Moreover, the EC 90 and EC 50 values found for the most active saponins in this study are similar to those reported for other active plant compounds [33]. These results are in agreement with previously reported data, confirming a high ovicidal activity of saponins from Medicago spp.…”
Section: Discussionsupporting
confidence: 93%
“…The saponins aescin and digitonin [17] and saponin fractions contained in Zizyphus joazeiro [16], Phytolacca icosandra [34] and Agave sisalana [18] showed 'in vitro' ovicidal activity against the nematodes of small ruminants. Similarly, the 'in vitro' ovicidal action of Combretum molle against eggs of H. contortus from sheep and of Ipomoea chiliantha, Tocoiena formosa and Aspilia latissima against the eggs of Haemonchus placei from cattle, have been attributed to their saponin content [33,35]. Biological effects of saponins are normally ascribed to their specific interaction with the cell membrane, causing changes in the cell permeability [20,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our work add to a growing body of literature demonstrating the use of ASE for the extraction of many classes of secondary metabolites (Borges et al, 2019; Ligor et al, 2018; Widelski et al, 2018). To the best of our knowledge, this is the first report on exhaustive extraction of cyclopeptides and other metabolites from Amanita samples.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, the extraction is a fully controlled process, which eliminates the problem of batch to batch variability caused by changing extraction conditions. Thus, ASE is a fast, efficient, and more environmentally friendly approach and has been proven to be a reliable and reproducible extraction technique for numerous types of natural matrices (Borges et al, 2019; Ligor, Ratiu, Kielbasa, Al‐Suod, & Buszewski, 2018; Widelski et al, 2018).…”
Section: Methodsmentioning
confidence: 99%